Tradisi Bajulo-Julo dalam Walimatul Ursy di Kampung Langgai Nagari Ganting Mudiak Utara Surantih Kecamatan Sutera Kabupaten Pesisir Selatan Perspektif Maslahah Mursalah - Abu Yasil; Basri Na’ali (Lembaga Yasin AlSys, 2026)
The bajulo-julo tradition in the implementation of walimatul ‘ursy in Langgai Village, Ganting Mudiak Utara Surantih Nagari, Sutera Subdistrict, Pesisir Selatan Regency, is a socio-religious practice that functions to help meet residents’ economic needs while strengthening bonds of brotherhood. This tradition is carried out in the form of money (pitih) and staple-food julo-julo, with a mechanism adjusted to price changes so that the value of mutual assistance is maintained. This study aimed to analyze the process of implementing bajulo-julo in walimatul ‘ursy and to examine this tradition from the perspective of Maslahah Mursalah. This study used a qualitative approach with a field research design. Data were collected through directed interviews with the head of the julo-julo, members of the julo-julo, and the community of Langgai Village, and were supported by documentation, literature, and relevant electronic sources. The data were analyzed systematically by integrating empirical findings and theoretical studies to obtain a comprehensive understanding of this traditional practice. The results showed that bajulo-julo in walimatul ‘ursy was implemented as a collective mechanism based on community participation to ease the economic burden of wedding celebration organizers and maintain social solidarity. From the perspective of Maslahah Mursalah, this tradition can be understood as a practice that has social benefit as long as it does not conflict with sharia principles. The conclusion of this study emphasizes that bajulo-julo plays an important role in maintaining the values of mutual cooperation, solidarity, and the welfare of the local community. These findings imply the importance of preserving local traditions that are aligned with socio-religious values and relevant to Islamic legal studies based on local wisdom.